Is there any relationship between unrecognized Celiac disease and unexplained infertile couples? - Karaca, Nilay; Yılmaz, Rabiye; Aktun, Lebriz Hale; Batmaz, Gonca; Karaca, Çetin (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Celiac Disease (CD) is a chronic autoimmune disease characterized by small intestinal malabsorbtion and diarrhea, triggered by the ingestion of food products containing gluten. There are studies reporting that some nutritional deficiencies and some factors related to immunity may cause a decrease in fertility as well as some problems in sperm parameters. The prevalence of CD in unexplained infertility (UEI) couples is not as high as that mentioned in some reports. There is no accurate knowledge about the prevalence of CD in a UEI couple. Materials and Methods: A total of 68 couples with UEI who were admitted at Türk Diyanet Vakfı 29 Mayıs Hospital Center of in vitro fertilization (IVF) between January and June 2014 were included in this prospective pilot study. The diagnosis of UEI was made with basic infertility tests. A history of CD was questioned in the initial evaluation. Anti-gliadin, anti-endomysial, and tissue transglutaminase antibodies as well as total IgA were tested. Gastroscopy was performed in patients with positive serologic tests. Histopathological CD diagnosis was made according to Marsh criteria. Results: The mean age of the study population was 33.40±4.59 years. Out of the 65 couples who were included into the study group, one of the five couples was positive for the autoantibodies (7.69%). Out of these 65 couples, none of them had autoantibody positivity at the same time in both partners. Anti-gliadin antibodies were found to be positive for two females out of five couples and in three male partners of the same group. Out of these five couples, only one male partner had all the antibodies as positive (1.5%). In the histopathological examination of patients with positive autoantibodies, only the patient in whom all autoantibodies were positive had findings compatible with Marsh IIIa gluten enteropathy. Only one couple had a diagnosis of CD (1.5%). Conclusion: In many studies, CD was shown to affect the reproductive system of women. CD may also cause a decrease in fertility in men by affecting sperm motility and androgen levels. Our study is based on a limited sample size. Our data should be confirmed in a larger cohort of subjects. These results suggest that investigation of both couples with a diagnosis of UEI may be more beneficial in clarifying the etiology.